XRAYS (eXamining Relevance of Articles to Young Survivors) Program Survey of Information Needs and Media Use by Young Breast Cancer Survivors and Young Women at High-Risk for Breast Cancer. Issue 12 (2nd December 2018) - Yi, Robin H. Pugh; Rezende, Lisa F.; Huynh, Julie; Kramer, Karen; Cranmer, Melissa; Schlager, Lisa; Dearfield, Craig T.; Friedman, Susan J.
ABSTRACT: Women age 45 years or younger with breast cancer, or who are at high-risk for breast cancer due to previously having the disease or to genetic risk, have distinct health risks and needs from their older counterparts. Young women frequently seek health information through the Internet and mainstream media, but often find it does not address their particular concerns, that it is difficult to evaluate or interpret, or even misleading. To help women better understand media coverage about new research, Facing Our Risk of Cancer Empowered (FORCE) developed the CDC-funded XRAYS (eXamining Relevance of Articles to Young Survivors) program. To assure that the XRAYS program is responsive to the community's needs, FORCE launched a web-based survey to assess where young women seek information about breast cancer, and to learn their unmet information needs. A total of 1, 178 eligible women responded to the survey. In general, the breast cancer survivors and high-risk women between ages 18–45 years who responded to this survey, are using multiple media sources to seek information about breast cancer risk, prevention, screening, and treatment. They place trust in several media sources and use them to inform their medical decisions. Only about one-third of respondents to this survey report discussing media sources with their health care providers. Current survey results indicate that, by providing credible information on the quality of evidence and reporting in media reports on cancer, XRAYS is addressing a key need for health information. Results suggest that it will be useful for XRAYS to offer reviews of articles on a broad range of topics that can inform decisions at each stage of risk assessment and treatment.